2010
DOI: 10.1073/pnas.0914772107
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide excision repair deficiency is intrinsic in sporadic stage I breast cancer

Abstract: The molecular etiology of breast cancer has proven to be remarkably complex. Most individual oncogenes are disregulated in only approximately 30% of breast tumors, indicating that either very few molecular alterations are common to the majority of breast cancers, or that they have not yet been identified. In striking contrast, we now show that 19 of 19 stage I breast tumors tested with the functional unscheduled DNA synthesis assay exhibited a significant deficiency of DNA nucleotide excision repair (NER) capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 52 publications
1
52
1
Order By: Relevance
“…The NER pathway is an important pathway for DNA damage repair, which mainly repairs the cyclobutane pyrimidine dimer, DNA adducts, and cross-linking between chains [33,34]. HR refers to the recombination of homologous DNA sequences, which mainly uses the homology of DNA sequences for recognition.…”
Section: Discussionmentioning
confidence: 99%
“…The NER pathway is an important pathway for DNA damage repair, which mainly repairs the cyclobutane pyrimidine dimer, DNA adducts, and cross-linking between chains [33,34]. HR refers to the recombination of homologous DNA sequences, which mainly uses the homology of DNA sequences for recognition.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the damaged site is restored by complexes consisting of DNA-Polδ/ε, RFC, and PCNA or, DNA-Polδ/ε and XRCC1 [70]. NER deficiency and its potential in the etiology of breast cancer was investigated in a study by Latimer et al [71], who showed a significant deficiency of NER capacity in stage I breast tumors relative to normal disease-free epithelial tissue, as tested by the functional unscheduled DNA synthesis assay. In tumor samples, the expression of 20 genes in NER pathway was decreased compared to normal tissue.…”
Section: Nucleotide Excision Repair (Ner) Pathwaymentioning
confidence: 99%
“…More recently, there are also PCR-based assays ( see Chapter 31), and flow cytometry-based assays [21, 22]. Recent studies using the UDS protocol in this chapter include functional analyses of primary cultures of human lymphocytes, breast and ovarian tissue, and early-stage breast tumors [2326]. …”
Section: Introductionmentioning
confidence: 99%